Echocardiogram-guided resuscitation versus early goal-directed therapy in the treatment of septic shock: a randomized, controlled, feasibility trial - Lanspa, Michael J. (J Intensive Care, 2018)
OBJECTIVE: Echocardiography is often used to guide septic shock resuscitation, but without evidence for efficacy. We conducted an intensive care unit (ICU)-based randomized controlled feasibility trial comparing echocardiography-guided septic shock resuscitation (ECHO) with early goal-directed therapy (EGDT). METHODS: We conducted a single center, randomized controlled feasibility trial at a 468-bed academic tertiary care center in Utah, USA. Adult patients with early septic shock were assessed and treated at defined intervals over 6 h using an echocardiogram-guided resuscitation protocol or a slightly modified EGDT protocol. Feasibility outcomes were fluid balance, dobutamine administration, and time to lactate clearance. The primary clinical outcome was changed in sequential organ failure assessment score at 48 h (delta SOFA). Secondary outcomes included inpatient mortality, ICU-free days, and ventilator-free days at 28 days. RESULTS: Thirty participants, 15 per group, were randomized and completed the study. Baseline characteristics were similar between groups. Patients were randomized within a median of 3.5 h of meeting inclusion criteria but had received a median of 3 L crystalloid by then. Fluid administration during the study protocol was similar in both groups (median ECHO 0 vs EGDT 1 L, p = 0.61). Eleven (73%) subjects in each arm received ≤ 1 L fluid. Dobutamine administration was also similar (20% vs 13%, p > 0.99). Twenty-one patients (70%) had lactate clearance prior to the first study assessment. No difference was observed in delta SOFA (median − 4 for ECHO vs − 6 for EGDT, p = 0.10) nor mortality (33% ECHO vs 20% EGDT, p = 0.68). CONCLUSIONS: No experimental separation was observed in this randomized, controlled feasibility trial. Early lactate clearance, coupled with substantial fluid administration before randomization, suggests that patients were already resuscitated before arrival in the ICU. Future trials of echocardiogram-guided sepsis resuscitation will likely need to enroll in the emergency department. TRIAL REGISTRATION: This study was retrospectively registered at clinicaltrials.gov (identifier NCT02354742, title Echo vs EGDT in severe sepsis and septic shock) on February 3, 2015. Registration was completed before review or analysis of any data. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40560-018-0319-3) contains supplementary material, which is available to authorized users.